Challenges and strategies in attacting voluntary blood donors in southern Tocantins (Research, Society and Development, 2023)
Introduction: The acquisition of blood is a challenge that begins with attracting donors, which requires means of searches and strategies for loyalty and acquisition of voluntary donors in blood banks. Objective: To identify the strategies and challenges for attracting voluntary blood donors in the south of Tocantins. Method: Descriptive, qualitative research. Conducted with 13 servants of a hemotherapy service in the south of Tocantins The interviews were recorded, transcribed and submitted to content analysis. Results: From the content analysis, the following categories emerged: strategies for attracting and retaining donors, challenges and difficulties in attracting donors, improvements in attracting donors, difficulties and strategies developed in attracting donors and opinion on attracting donors, which were presented and discussed in detail. according to the relevant literature. Conclusion: The recruitment of donors encompasses external actions with the community and internal actions with the donors themselves. Most interviewees recognize their role in attracting and maintaining donors, mainly through the service, which should be welcoming and clarifying doubts.